A novel nomogram and prognostic factor for metastatic renal cell carcinoma survival in the era of immune checkpoint inhibitors (ICIs) - Alradhi, Mohammed; Zhang, Zewen; Safi, Mohammed; Al-danakh, Abdullah; Aldhbi, Mokhtar; Baldi, Salim; kui, Li; Alradhi, Abdulaziz; Hamri, Saeed Bin; Lun lo, Ka; Zhao, Yi; Jin, Yang (Frontiers in Pharmacology, 2023)
Patients with metastatic renal cell cancer (mRCC) for whom surgery is ineffective may experience a poor prognosis. The different sites where cancer has spread, and the different ways to treat it in the immune checkpoint inhibitors (ICIs) era could help clinical decision-making. In this study, individuals with mRCC were selected from the SEER database between 2015 and 2016 based on the Food and Drug Administration (FDA) approval of ICIs. A total of 4011 mRCC patients were studied (2239 with lung metastasis vs 797 with liver metastasis in the ICI period).The age ≤ 64 years and male were the majority in all cases of mRCC.When the two groups (lung metastasis and liver metastasis ) were compared,the liver metastasis group had more bone metastasis than the lung metastasis group (41.8% vs. 34.1%, P<0.001), but the lung metastasis group had more brain metastasis (8.9% vs. 11.5%) (P=0.023). In a study of overall survival (OS) in the ICI era for mRCC, we found that lung metastasis was significantly associated with improved survival compared to liver metastasis (P < 0.001: 7 months vs. 4 months). This survival advantage restricted in lung metastasis group of mRCC after adjusting age, sex, race, marital status, histological type, metastasis to bone, and brain, origin, radiotherapy record chemotherapy record, surgery on multivariable using Cox proportional hazard model (HR=1.407; 95% CI=1. 269-1.560; P< 0.001). The OS difference between the variables of lung metastasis and liver metastasis was noted among most of the variables, with survival benefits restricted to patients in lung metastasis in the ICI era. patients who had undergone chemotherapy and surgery were strongly positive predictors for better OS(HR=0.427;95% CI=0.379-0.481;P< 0.001), (HR=0.371;95% CI=0.311-0.444;P<0.001), and(HR=0.313;95% CI=0.264-0.372;P< 0.001),(HR=0.427;95% CI=0.320-0.568;P< 0.001) in lung metastasis group and liver metastasis group.The c-index of the prognostic nomogram for OS prediction was 0.74 and 0.73. This study found that patients with lung metastasis who received ICI had better survival than those with liver metastasis .Chemotherapy and surgery enhanced survival in kidney cancer patients, whereas radiation had little impact. We developed a complete and realistic nomogram for mRCC patients based on distant metastases to the lung and liver.